Pengaruh Proses Pembayaran Pajak Kendaraan Bermotor di Samsat Terhadap Kepuasan Masyarakat Kota Serang - Alvina Novanka; Munawaroh Munawaroh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study looks at service quality. that affects community satisfaction in paying motor vehicle tax at Serang City Samsat. Quality factors include overall, responsiveness, assurance, empathy, and physical evidence. This study's objective is to look into the ways that the public. This This study's goal is to investigate public perceptions regarding caliber of services rendered by Samsat and provide suggestions for improvement. According to various sources, good public services must meet people's needs and provide a satisfying experience, but taxpayers can become dissatisfied with problems such as complicated procedures and long time.